Developmental amnesia: Effect of age at injury - Vargha-Khadem, F. (National Academy of Sciences, 2003)
Hypoxic–ischemic events sustained within the first year of life can result in developmental amnesia, a disorder characterized by markedly impaired episodic memory and relatively preserved semantic memory, in association with medial temporal pathology that appears to be restricted to the hippocampus. Here we compared children who had hypoxic–ischemic events before 1 year of age (early group, n = 6) with others who showed memory problems after suffering hypoxic–ischemic events between the ages of 6 and 14 years (late group, n = 5). Morphometric analyses of the whole brain revealed that, compared with age-matched controls, both groups had bilateral abnormalities in the hippocampus, putamen, and posterior thalamus, as well as in the right retrosplenial cortex. The two groups also showed similar reductions (≈40%) in hippocampal volumes. Neuropsychologically, the only significant differences between the two were on a few tests of immediate memory, where the early group surpassed the late group. The latter measures provided the only clear indication that very early injury can lead to greater functional sparing than injury acquired later in childhood, due perhaps to the greater plasticity of the infant brain. On measures of long-term memory, by contrast, the two groups had highly similar profiles, both showing roughly equivalent preservation of semantic memory combined with marked impairment in episodic memory. It thus appears that, if this selective memory disorder is a special syndrome related to the early occurrence of hypoxia-induced damage, then the effective age at injury for this syndrome extends from birth to puberty.